(3JPgjH GdJgPjHs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3MQa GdSjf SGHb Hf fGLjI , Yf CHj SdGe hYfg gGTe GHf HdGd s
(3BNQgG (B:s
(3bGd GHf MjGf (B: (3eSJbje GdMOjK gPG BNQ GdeLdO GdKGfi hjJdhg ai GdeLdO GdKGdK YHO GdQMef Hf YHO GdbGOQi (B( (3?(B) s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs